2004
DOI: 10.1089/neu.2004.21.932
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Chloride Reinforces the Regeneration-Promoting Effect of Chondroitinase ABC on Rubrospinal Neurons after Spinal Cord Injury

Abstract: CitationJournal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
1
20
1
1
Order By: Relevance
“…Thus, a dual effect of LiCl in cell survival and axon growth is likely to be responsible for these results. Indeed, a single application of LiCl after spinal cord lesion does not promote the regeneration of rubrospinal axons (Yick et al 2004), and the over-expression of Bcl-2 does not stimulate axon regeneration per se in several lesion models (Chen and Tonegawa 1998;Chierzi et al 1999;Inoue et al 2002;Sole et al 2004). In contrast, LiCl has recently been used after spinal cord lesion (Dill et al 2008), and the results contrast with those reported by Alabed and co-workers (Alabed et al 2007; Society for Neuroscience) with respect to the inhibition of GSK3b.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, a dual effect of LiCl in cell survival and axon growth is likely to be responsible for these results. Indeed, a single application of LiCl after spinal cord lesion does not promote the regeneration of rubrospinal axons (Yick et al 2004), and the over-expression of Bcl-2 does not stimulate axon regeneration per se in several lesion models (Chen and Tonegawa 1998;Chierzi et al 1999;Inoue et al 2002;Sole et al 2004). In contrast, LiCl has recently been used after spinal cord lesion (Dill et al 2008), and the results contrast with those reported by Alabed and co-workers (Alabed et al 2007; Society for Neuroscience) with respect to the inhibition of GSK3b.…”
Section: Discussionmentioning
confidence: 90%
“…The GSK3b-mediated inhibition of axon regeneration of lesioned neurons has been studied mainly through the use of pharmacological treatments with LiCl. Indeed, LiCl treatment combined with chondroitinase ABC (Yick et al 2004) promotes axon regeneration of ganglion cells in the retina (Huang et al 2003) and rubrospinal tract. These effects correlate with increased Bcl-2 expression and GSK3b inhibition (Yick et al 2004;Dill et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlated with decreases in eIF-2B, suggesting trauma-induced activation of GSK-3b may lead to alterations in protein synthesis. In addition, in adult rats receiving a unilateral hemisection at the seventh cervical spinal cord segment, phosphoSer9-GSK-3b was increased by administration of lithium chloride, a GSK regulator with neuroprotective properties (35). The inhibition of GSK by lithium enhanced the ability of chondroitinase ABC to promote regeneration of axotomized rubrospinal tract neurons.…”
Section: Gsk-3mentioning
confidence: 98%
“…На модели крыс с повреждени-ем спинного мозга, вызванным односторонней гемисек-цией, при комбинированном лечении препаратами лития с хондроитиназой был достигнут синергичный эффект. Отмечены увеличение регенерации аксонов в руброспи-нальном тракте и улучшение движения передних конеч-ностей [69]. Данный эффект терапии осуществлялся за счет увеличения секреции BDNF [70], который усиливает клеточное деление и дифференцировку клеток-предше-ственников нейронов, наряду с уменьшением активации микроглии и макрофагов [71].…”
Section: другие направления использования лития в медицинеunclassified